CHANGES IN A SODIC SOIL AFTER GYPSUM APPLICATION UNDER DRYLAND CONDITIONS - Elena Bonadeo; Ines Moreno; Andres Baranda; Cecilia Milan (European Scientific Journal, ESJ, 2014)
In the Province of Cordoba Argentina there are 2.803.000 ha of soils that are sodic from a depth of around 20 cm, 93.000 of which are in San Martin department where the study area is situated. These soils, generally loam - textured soils, occur in mildly depressed areas. Paddocks frequently show uneven crop growth, named “patchy growth”, where sectors of lower plants alternate with sectors of higher plants that look normal (N). The main objective of this study is, then, to evaluate the effect of gypsum on soil properties. The treatments were MD (maximum dose) at a rate of 3350 kg ha-1, AD (agronomic dose) at a rate of 1340 kg ha-1 of gypsum and C without gypsum. Gypsum was spread manually over the soil. Three years later, more gypsum was applied to AD (1340 kg ha-1). Five years after the first application of gypsum, in the second horizon, the higher dose of gypsum (MD) lowered soil pH (H2O), soil strength and water content held at all matric potentials, and also increased soil permeability increased. The lower and partitioned dose (AD) had a detrimental or no effect on the properties evaluated. Probably the lower dose was insufficient to modify the subsuperficial permeability and leaching was decreased.